Robustness Comparison of Emerging Devices for Portable Applications. (28th February 2012) - Pable, S. D.; Kafeel, Mohd. Ajmal; Kureshi, A. K.; Hasan, Mohd.
Abstract : Extensive development in portable devices imposes pressing need for designing VLSI circuits with ultralow power (ULP) consumption. Subthreshold operating region is found to be an attractive solution for achieving ultralow power. However, it limits the circuit speed due to use of parasitic leakage current as drive current. Maintaining power dissipation at ultralow level with enhanced speed will further broaden the application area of subthreshold circuits even towards the field programmable gate arrays and real-time portable domain. Operating the Si-MOSFET in subthreshold regions degrades the circuit performance in terms of speed and also increases the well-designed circuit parameter spreading due to process, voltage, and temperature variations. This may cause the subthreshold circuit failure at very low supply voltage. It is essential to examine the robustness of most emerging devices against PVT variations. Therefore, this paper investigates and compares the performance of most promising upcoming devices like CNFET and DG FinFET in subthreshold regions. Effect of PVT variation on performance of CNFET and DG FinFET has been explored and it is found that CNFET is more robust than DG-FinFET under subthreshold conditions against PVT variations.